Catheter-based Closure of a Post-infective Aortic Paravalvular Pseudoaneurysm Fistula With Severe Regurgitation After Two Valve Replacement Surgeries: A Case Report - Onorato, Eustaquio Maria; Vercellino, Matteo; Masoero, Giovanni; Monizzi, Giovanni; Sanchez, Federico; Muratori, Manuela; Bartorelli, Antonio L. (Frontiers in Cardiovascular Medicine, 2021)
Backgsround: Infective endocarditis (IE) of prosthetic valves is a dire complication of cardiac valve replacement surgery and is associated with high rates of morbidity and mortality. Case Summary: A 72-year-old woman with multiple comorbidities underwent surgical replacement of the aortic valve with a mechanical prosthetic valve after recurrent IE. After nine months, IE recurred and the mechanical valve was surgically replaced with a bioprosthetic valve. Three years later, severe heart failure developed due to severe paravalvular leak (PVL) caused by an aortic annulus abscess complicated by a paravalvular pseudoaneurysm fistula (PPF). The patient was deemed at prohibitive surgical risk and a catheter-based PVL closure procedure was planned. However, the interventional procedure was delayed several months due to the Covid-19 pandemic with progressive heart failure worsening. Despite an acute satisfactory result of the PPF transcatheter closure and a significant clinical improvement, the patient died 10 months later due to multiorgan failure. It is likely that this was due, at least in part, to the long treatment delay caused by the unprecedented strain on the healthcare system. Discussion: In patients at high surgical risk, early diagnosis and prompt interventional treatment of severe PVL are crucial for improving expectancy and quality of life. However, the recent outbreak of COVID-19 caused deferral of elective and semi-elective structural heart disease procedures (SHD) as in our case. Thus, a proactive and vigilant stance on managing SHD should be a priority even in the context of the COVID-19 pandemic.